Caracterização do escoamento de ar em um motor de combustão interna utilizando mecânica dos fluidos computacional - Leonardo Guimaraes Fonseca (2014)
In cylinder transient flow field characterization of an internal combustion engine using computational fluid dynamics solved by finite volume method is presented. In cylinder cold flow parameters are analyzed for a number of engine operation conditions attempting to determine which the best ones for engine performance optimization are. Expert system ES-ICE is used to generate moving mesh and simulate piston and valves movements, thus allowing the calculation of full transient flow field during the entire engine cycle. Turbulence model RNG k- is selected for turbulence calculation, once it has good performance in describing in cylinder flow field over many papers of the literature when its results are compared to experimental data, and also for its relatively low computational demanding. A grid independence proceeding is used in order to present reliable results for the entire analysis. The bottom dead center mesh is chosen as reference of the analysis period for mesh refinement, and the results for velocity average at specific sections are used to verify the quality of the results through different meshes and choose the one with best compromising between quality of results and computational demand. Validation is achieved applying the model to a single cylinder research engine and comparing its results with experimental ones obtained at the same research engine. Simulations of the transient in cylinder flow field are made for eight engine crankshaft rotational speeds, and for each speed three values of valve overlapping are also simulated, namely 0, 30 and 60 crank angle degrees (CAD). The main objective is to characterize the in cylinder flow in terms of vortex intensity during intake and compression strokes, amount of air trapped into the cylinder and analyse tumble and swirl for each one of the valve overlapping angles mentioned. Results show the characteristic of the flow field inside the object cylinder, which has average swirl as its main vortex for all operation conditions under analysis. Tumble vortex has the second average intensity for the major cases; meanwhile the cross tumble vortex average value is important only for a few cases. Among the valve overlapping comparison, 30 CAD shows the best average results, as for intensity and stability of swirl vortex, as for volumetric efficiency, thus it is the one which has the greater probability to offer greater combustion efficiency. It can also be seen through the results how CFD can aid the evaluation of those important quantities for any internal combustion engine.